2015
DOI: 10.1017/s1355617715000181
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Effect of Dopamine Medication on Cognition in Parkinson’s Disease: Relationship to Side of Motor Onset

Abstract: Parkinson's disease (PD) is characterized by asymmetric motor symptom onset attributed to greater degeneration of dopamine neurons contralateral to the affected side. However, whether motor asymmetries predict cognitive profiles in PD, and to what extent dopamine influences cognition remains controversial. This study evaluated cognitive variability in PD by measuring differential response to dopamine replacement therapy (DRT) based on hemispheric asymmetries. The influence of DRT on cognition was evaluated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 86 publications
2
22
0
Order By: Relevance
“…The lower tapping accuracy in the ON (hyperdopaminergic) state may be due to the hypothesis of Vaillancourt et al [24]: a dopamine overdose effect in the ventral and anterior striatum could negatively affect the cognitive challenge of tapping both quickly and accurately. In fact, multiple cognitive domains may be adversely affected by dopamine flooding [25]. The blinded video analysis suggested dyskinesia did not affect accuracy, regardless of the presence of dyskinesia in the upper or lower extremity.…”
Section: Discussionmentioning
confidence: 99%
“…The lower tapping accuracy in the ON (hyperdopaminergic) state may be due to the hypothesis of Vaillancourt et al [24]: a dopamine overdose effect in the ventral and anterior striatum could negatively affect the cognitive challenge of tapping both quickly and accurately. In fact, multiple cognitive domains may be adversely affected by dopamine flooding [25]. The blinded video analysis suggested dyskinesia did not affect accuracy, regardless of the presence of dyskinesia in the upper or lower extremity.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing bradykinesia and increasing the speed and fluency of movements and motor responses is the chief beneficial effect of dopaminergic therapy in PD (Espay et al, 2011 ; Macerollo et al, 2016 ). There is little evidence to suggest that dopaminergic therapy generally slows cognitive processes and in fact there is support that it hastens them (Cools et al, 2001 ; Shook et al, 2005 ; Hood et al, 2007 ; Righi et al, 2007 ; MacDonald and Monchi, 2011 ; MacDonald et al, 2011 ; Hanna-Pladdy et al, 2015 ). In contrast, as we review in sections below, dopaminergic therapy has been shown to increase response inhibition as well as to promote adopting a more conservative response criterion, consistent with our explanation for increased Go Timeouts in the ON-state for PD patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides deficient dopamine, other factors also contribute to cognitive deficits in the disease, including structural changes to the brain ( 18 , 19 ), and accumulation of amyloid plaques and tau protein ( 20 , 21 ). Moreover, the role of dopamine, and influence of dopaminergic medication, in cognition is variable, as previous studies show both improvement and worsening of different cognitive functions by medication, depending on task demands and individual differences in baseline dopamine levels ( 22 , 23 ), as well as side of motor symptom onset ( 24 ).…”
Section: Introductionmentioning
confidence: 99%